دور الحوافز في تحقيق الالتزام الوظيفي دراسة مسحية على العاملين في شركة سيريَتل للاتصالات - مرهج منذر; علاء الدين باسل (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الاقتصادية والقانونية, 2018)
The objective of this study is to study the relationship between incentives (Material, moral) and functional commitment (Affective, Continuance, Normative). The researchers used the questionnaire as a tool for data collection, they distributed this questionnaire to a random sample of 352 workers at Syriatel Communications, The researchers used the Pearson coefficient to study the relationship between incentives as an independent variable and functional commitment as a dependent variable. The researchers used the SPSS program version 20 to conduct statistical tests of research hypotheses. The research found that there was a strong moral relationship between the Material and moral incentives applied in Syriatel with the three types of functional commitment, but in varying degrees, and the strongest relationship between Material incentives and affective commitment, the Pearson correlation coefficient was / 0.989/. The researchers recommended the need to increase transportation allowance for employees; taking into account the views and suggestions of employees; and work to strengthen the organizational culture that emphasizes the sense of belonging to the company and the loyalty to it. يهدف هذا البحث إلى دراسة العلاقة بين الحوافز(المادية, المعنوية)، والالتزام الوظيفي (العاطفي, المستمر, المعياري), حيث قام الباحثان باستخدام الاستبانة كأداة للدراسة وجمع البيانات، وقاما بتوزيع هذه الاستبانة على عينة عشوائية بلغت /352/ عاملاً في شركة سيريَتل للاتصالات، واعتمد الباحثان على معامل بيرسون لدراسة العلاقة بين الحوافز كمتغير مستقل، وبين الالتزام الوظيفي كمتغير تابع، وقد استخدم الباحثان برنامج SPSS بالإصدار 20 في إجراء الاختبارات الإحصائية لفرضيات البحث. توصل البحث إلى وجود علاقة معنوية قوية بين كل من الحوافز المادية والمعنوية المطبقة في شركة سيريَتل مع انواع الالتزام الوظيفي الثلاثة ولكن بنسب متفاوتة, وكانت أقوى العلاقات بين الحوافز المادية والالتزام العاطفي حيث بلغ قيمة معامل الارتباط بيرسون/0.989/. وأوصى الباحثان بضرورة زيادة بدل المواصلات للعاملين؛ ومراعاة أراء ومقترحات العاملين؛ والعمل على تعزيز الثقافة التنظيمية التي تؤكد على شعور الانتماء لشركة سيريَتل والولاء لها.